Patchwork as A Tool to Build Creativities in Semarang’s Orphanage - Elizabeth Ika Hesti Aprilia Nindia Rini (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2019)
This activities goal is to remind the importance of educating children about life skills and to develop their creativity in order to be able to create and produce functional goods that have economic value so that children may also learn entrepreneurship. Through this community service activity (pengabdian kepada masyarakat), children are encouraged to create ideas and develop their imagination, and skills to create patchwork. This PKM that designed to contain educational, entertainment and attractive elements are expected to foster self-confidence, independence, constructive social abilities and stimulate entrepreneurial  spirit.Keywords: patchwork, life skills education, entrepreneurship.